(New page: Going through the system first and then the time shift: x[n] -> y[n] = (k + 1)^2x[n-(k+1)] y[n] -> z[n] = y[n-1] = (k+1)^2x[n-1-(k+1)] Going through the time shift first and then th...) |
|||
Line 1: | Line 1: | ||
+ | |||
+ | == A == | ||
+ | |||
+ | |||
Going through the system first and then the time shift: | Going through the system first and then the time shift: | ||
Line 17: | Line 21: | ||
Since the two results are the same, the system is time invariant. | Since the two results are the same, the system is time invariant. | ||
+ | |||
+ | |||
+ | |||
+ | == B == | ||
+ | |||
+ | The input would have to be u[n] |
Latest revision as of 13:44, 12 September 2008
A
Going through the system first and then the time shift:
x[n] -> y[n] = (k + 1)^2x[n-(k+1)]
y[n] -> z[n] = y[n-1]
= (k+1)^2x[n-1-(k+1)]
Going through the time shift first and then the system:
x[n] -> y[n] = x[n-1]
y[n] -> z[n] = (k+1)^2y[n-(k+1)]
= (k+1)^2x[n-1-(k+1)]
Since the two results are the same, the system is time invariant.
B
The input would have to be u[n]